Licarin-B Exhibits Activity Against the Toxoplasma gondii RH Strain by Damaging Mitochondria and Activating Autophagy - Zhang, Jili; Si, Hongfei; Lv, Kun; Qiu, Yanhua; Sun, Jichao; Bai, Yubin; Li, Bing; Zhou, Xuzheng; Zhang, Jiyu (Frontiers in Cell and Developmental Biology, 2021)
Toxoplasma gondii is an obligate intracellular pathogen that infects warm-blooded animals and humans. However, side effects limit toxoplasmosis treatment, and new drugs with high efficiency and low toxicity need to be developed. Natural products found in plants have become a useful source of drugs for toxoplasmosis. In this study, twenty natural compounds were screened for anti-T. gondii activity by Giemsa staining or real-time fluorescence quantitative polymerase chain reaction (qPCR) in vitro. Among these, licarin-B from nutmeg exhibited excellent anti-T. gondii activity, inhibiting T. gondii invasion and proliferation in a dose-dependent manner, with an EC50 of 14.05 μg/mL. In the in vivo, licarin-B treatment significantly reduced the parasite burden in tissues compared to no treatment, protected the 90% infected mice from to death at 50 mg/kg.bw. Flow cytometry analysis suggested a significant reduction in T. gondii survival after licarin-B treatment. Ultrastructural changes in T. gondii were observed by transmission electron microscopy (TEM), as licarin-B induced mitochondrial swelling and formation of cytoplasmic vacuoles, an autophagosome-like double-membrane structure and extensive clefts around the T. gondii nucleus. Furthermore, MitoTracker Red CMXRos, MDC and DAPI staining showed that licarin-B promoted mitochondrial damage, autophagosome formation, and nuclear disintegration, which were consistent with the TEM observations. Together, these findings indicate that licarin-B is a promising anti-T. gondii agent that potentially functions by damaging mitochondria and activating autophagy, leading to T. gondii death.